The Effectiveness of Reality Therapy in Improving Learning Motivation and Discipline - Nurjanah, Anisa Siti; Sanyata, Sigit; Zatrahadi, M Fahli (Psikopedagogia, 2020)
This meta-analytical study aimed to examine the effectiveness of reality therapy in enhancing students learning motivation and discipline. Seven experimental studies were selected as the sample of the study using purposive sampling technique. These selected studies reported the effect of reality therapy on learning motivation and discipline. The analysis was done using pre-post contrast meta-analysis. The calculation result showed a weighted mean effect score of 2.818. The mean effect size score is the parameter that represents effective contribution. This positive score indicates that the post-test score is higher than the pre-test score. Accordingly, it could be concluded that reality therapy is effective for enhancing learning motivation and discipline.